Takt complementing Last Planner® System on residential construction projects. - William Power (Construction Economics and Building)
Ireland is experiencing a national housing crisis, and this is replicated across many developed economies. This challenges governments and housebuilders to increase production whilst balancing challenging human resource and supply chain constraints. Lean construction methodologies have enhanced project delivery in other sectors of the industry. This study evaluates the outcomes of Last Planner System and Takt planning implementation on two residential projects.